Implementasi Metode Pembelajaran Berbasis Kelompok (Group Investigation) dalam Meningkatkan Partisipasi Aktif Siswa Kelas XI pada Pembelajaran Akidah Akhlak di MAN 1 Kota Bima - Nurinsa Safitriani; Irwan Irwan; Ferdiansyah Ferdiansyah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to describe the implementation of the group-based learning method (Group Investigation) in improving the active participation of eleventh-grade students in Akidah Akhlak learning at MAN 1 Bima City. The main focus is to obtain in-depth information regarding the implementation of the Group Investigation learning model and its impact on enhancing students’ active participation. The research method used is descriptive qualitative. Qualitative research emphasizes the quality and meaning behind phenomena, while the descriptive approach is used to narrate individual or group experiences through documentation and personal analysis. The results show that the implementation of the Group Investigation learning model is carried out through six stages: identifying topics and organizing them into research groups (grouping), planning investigations within groups (planning), conducting investigations (investigating), preparing the final report (organizing), presenting the final report (presenting), and evaluating achievements (evaluating). The implementation of the group-based learning method (Group Investigation) has proven to be highly effective in increasing the active participation of eleventh-grade students in Akidah Akhlak learning at MAN 1 Bima City. Overall, the application of the cooperative Group Investigation model encourages the creation of an interactive learning experience. Students become more confident in participating in discussions, expressing their opinions, and collaborating within groups to complete assigned tasks. Based on the analysis and discussion, it can be concluded that the cooperative learning model of the Group Investigation type provides opportunities for students to act as active learners as well as peer educators within their groups. Open interaction among group members fosters a pattern of cooperation that allows students to share knowledge, strengthen understanding, and enhance social values such as mutual trust, openness, and shared responsibility.